MoO3 / C co-coated micro-expansion microcrystalline graphite / Fe3O4 lithium ion battery negative electrode material as well as preparation method and application thereof

By using the sol-gel method to prepare microcrystalline graphite/Fe3O4 composite materials in the negative electrode material of lithium-ion batteries, and using the liquid phase coating method to perform MoO3/C coating, the problems of poor microcrystalline graphite performance and Fe3O4 volume expansion are solved, and higher specific capacity and cycling stability are achieved.

CN119601632AActive Publication Date: 2025-03-11LIAONING TECHNICAL UNIVERSITY

Patent Information

Application Number
CN202411782048.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-11
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

Microcrystalline graphite has problems with poor reversible specific capacity and rate performance in the negative electrode materials of lithium-ion batteries, and the volume expansion of Fe3O4 during charging and discharging leads to unstable structure.

Method used

The micro-expanded microcrystalline graphite/Fe3O4 composite material was prepared by the sol-gel method, and the MoO3/C composite material was coated on its surface by liquid phase coating method to form a core-shell structure to inhibit the volume expansion of Fe3O4.

Benefits of technology

It improves the specific capacity and cycle stability of lithium-ion batteries, and enhances the structural stability and electrochemical properties of the negative electrode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601632A_ABST
    Figure CN119601632A_ABST
Patent Text Reader

Abstract

The invention discloses a MoO3 / C co-coated micro-expansion microcrystalline graphite / Fe3O4 lithium ion battery negative electrode material and a preparation method and application thereof, and relates to the technical field of new material preparation and new energy, and the preparation method comprises the following steps: preparing a micro-expansion microcrystalline graphite / Fe3O4 composite material by taking micro-expansion microcrystalline graphite as a matrix and adopting a sol-gel method; and preparing the MoO3 / C co-coated micro-expansion microcrystalline graphite / Fe3O4 composite material by taking the micro-expansion microcrystalline graphite / Fe3O4 composite material as a matrix and adjusting the addition amount of ammonium molybdate and citric acid by adopting a liquid phase coating method, and using the MoO3 / C co-coated micro-expansion microcrystalline graphite / Fe3O4 composite material as a lithium ion battery negative electrode material. Under the current density of 0.1 A / g, the coating material has the first specific discharge capacity of 987.3 mAh / g, the first coulombic efficiency is 81.6%, and the coating material still has the specific discharge capacity of 853.2 mAh / g after 100 cycles. The lithium storage performance such as reversible capacity of the high-purity microcrystalline graphite lithium ion battery negative electrode material is remarkably improved, and the application potential and commercial value of microcrystalline graphite are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of new material preparation and new energy technology, and specifically relates to a MoO3 / C co-coated micro-expanded microcrystalline graphite / Fe3O4 lithium ion battery negative electrode material and a preparation method thereof, and application in lithium ion batteries. Background Art

[0002] At present, due to the insufficient development and utilization of microcrystalline graphite resources and limited investment in high-end technology development, the deep processing level of graphite products is relatively low, mainly staying at the stage of preliminary processing and simple treatment of raw materials, resulting in serious waste of mineral resources. In view of the small grains of microcrystalline graphite and its isotropic structural characteristics, it shows great application potential in the field of new lithium-ion power batteries. However, when used as a negative electrode material for lithium-ion batteries, microcrystalline graphite still faces the problem of poor reversible specific capacity and rate performance. Oxidation of microcrystalline graphite to increase the interlayer spacing and pore structure is an effective means to increase the lithium storage capacity; compounding microcrystalline graphite with the oxide of conductive metal Fe can significantly increase the lithium storage capacity, but the metal oxide produces a large volume expansion during the process of lithium removal / intercalation, making the structure unstable. Summary of the invention

[0003] In order to suppress the volume expansion of Fe3O4 during charging and discharging and improve the lithium storage capacity of microcrystalline graphite lithium ion battery negative electrode materials, the purpose of the present invention is to provide a MoO3 / C co-coated micro-expanded microcrystalline graphite / Fe3O4 lithium ion battery negative electrode material and its preparation method and application. With microcrystalline graphite as the core, the micro-expanded microcrystalline graphite and nano Fe3O4 are compounded, and the precursor is carbonized through a specific process to form a core-shell structure, which can not only increase the specific capacity of the lithium ion battery, but also effectively suppress the volume expansion of metal oxides and enhance the structure and cycle stability of the microcrystalline graphite negative electrode material.

[0004] To further achieve the above object, the present invention adopts the following technical scheme: a method for preparing a MoO3 / C co-coated micro-expanded microcrystalline graphite / Fe3O4 lithium ion battery negative electrode material, comprising:

[0005] Micro-expanded microcrystalline graphite / Fe3O4 composite materials were prepared by sol-gel method with micro-expanded microcrystalline graphite as matrix.

[0006] Then, the micro-expanded microcrystalline graphite / Fe3O4 composite material was used as the matrix and the MoO3 / C co-coated micro-expanded microcrystalline graphite / Fe3O4 composite material was prepared by using a liquid phase coating method by changing the addition amounts of ammonium molybdate and citric acid.

[0007] Optionally, the preparation of the micro-expanded microcrystalline graphite / Fe3O4 composite material by a sol-gel method comprises the following steps:

[0008] Step (1): weigh 0.3-0.6 g of ferric nitrate, add 20-40 ml of deionized water, and sonicate for 30-40 min;

[0009] Step (2): add 0.1-0.4 g of citric acid, stir in a magnetic stirring water bath at 50-70° C., and add ammonia water dropwise until the solution is neutral;

[0010] Step (3): When the ferric nitrate-citrate mixed solution is in a gelatinous state, 0.1 to 0.3 g of ultrasonically dispersed micro-expanded microcrystalline graphite is added, and heating and stirring are continued until the water is evaporated to dryness, thereby obtaining a composite material precursor;

[0011] Step (4): Place the prepared precursor into an Ar gas protected tubular furnace, heat it to 300-400°C at a rate of 5-7°C / min, keep it warm for 1-2h, and cool it to room temperature to prepare micro-expanded microcrystalline graphite / Fe3O4 composite materials with different Fe3O4 mass fractions.

[0012] Furthermore, the microcrystalline graphite is micron-sized microcrystalline graphite with a slightly expanded boundary of about 5 μm, and the Fe3O4 prepared in step (4) is a nano-sized particle, and the two form a micro-nano composite structure.

[0013] Optionally, the liquid phase coating method, by changing the addition amount of ammonium molybdate and citric acid, prepares the MoO3 / C co-coated micro-expanded microcrystalline graphite / Fe3O4 composite material, comprising the following steps:

[0014] Step (1): weigh 0.5-2 g of micro-expanded microcrystalline graphite / Fe3O4 composite material, disperse it in 20-50 ml of anhydrous ethanol, and ultrasonicate it for 20-50 min;

[0015] Step (2): weigh 0.2-0.8 g of ammonium molybdate and 0.0035-0.0087 g of citric acid, add 20-40 ml of deionized water, and sonicate until completely dissolved;

[0016] Step (3): stirring in a water bath at 60-90° C., adding the dispersed micro-expanded microcrystalline graphite / Fe3O4 composite material and continuing to stir until the water is evaporated;

[0017] Step (4): drying in a vacuum oven at 50-80°C;

[0018] Step (5): placing the prepared coating material into an Ar gas protected tubular furnace, heating it to 200-460°C at a rate of 5-7°C / min, keeping it warm for 1-2 hours, and naturally cooling it to room temperature to obtain a MoO3 / C co-coated micro-expanded microcrystalline graphite / Fe3O4 composite material.

[0019] As described above, the MoO3 / C coating material and Fe3O4 prepared in step (5) are distributed in the form of microspheres on the surface and edge of the micro-expanded microcrystalline graphite.

[0020] A MoO3 / C co-coated micro-expanded microcrystalline graphite / Fe3O4 composite material prepared by the aforementioned preparation method.

[0021] An application of the aforementioned micro-expanded microcrystalline graphite / Fe3O4 composite material in a negative electrode of a lithium-ion battery.

[0022] An application of the MoO3 / C co-coated micro-expanded microcrystalline graphite / Fe3O4 composite material prepared as described above in the negative electrode of a lithium-ion battery.

[0023] Technical advantages of the present invention:

[0024] (1) The present invention uses micro-expanded microcrystalline graphite as a raw material and adopts a sol-gel method to prepare a micro-expanded microcrystalline graphite / Fe3O4 composite material. Since the microcrystalline graphite has fine grains and isotropic, the number of lithium ion diffusion channels increases, and the reversible lithium storage capacity is higher than that of flake graphite. In order to increase the lithium storage capacity, the use of micro-expanded microcrystalline graphite can increase the number of lithium ion pore channels. However, due to its small size, microcrystalline graphite is generally slightly oxidized at the edges. Therefore, using slightly oxidized microcrystalline graphite as a matrix, nano-sized Fe3O4 is mainly filled into the edge pores of the micro-expanded microcrystalline graphite to form a micro-nano structure. The two have a high degree of bonding and can form a stable lithium storage structure. The sol-gel method is an effective means to prepare micro-nano composite materials.

[0025] (2) The present invention uses micro-expanded microcrystalline graphite / Fe3O4 as raw materials and adopts a liquid phase coating method to prepare a MoO3 / C co-coated micro-expanded microcrystalline graphite / Fe3O4 composite material. Since Fe3O4 expands greatly in volume during the charge and discharge of lithium-ion batteries, a composite material of MoO3 and C with high mechanical strength is used to coat the edges of the composite material to form a core-shell structure with micro-expanded microcrystalline graphite / Fe3O4 as the core and MoO3 / C composite material as the shell, which can inhibit the volume expansion effect of the composite material and enhance the cycle stability of lithium-ion batteries. The liquid phase coating method promotes the full mixing of the reactants, which is conducive to the formation of a uniformly coated core-shell structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is the microstructure morphology of the micro-expanded microcrystalline graphite / Fe3O4 composite material prepared in Example 1 of the present invention.

[0027] Figure 2 This is the microstructure morphology of the MoO3 / C co-coated micro-expanded microcrystalline graphite / Fe3O4 composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] A method for preparing a MoO3 / C co-coated micro-expanded microcrystalline graphite / Fe3O4 lithium ion battery negative electrode material comprises the following steps:

[0030] (1) Weigh 0.3-0.6 g of ferric nitrate, add 20-40 ml of deionized water, and sonicate for 30-40 min;

[0031] (2) Add 0.1-0.4 g of citric acid, stir in a magnetic stirring water bath at 50-70°C, and add ammonia water dropwise until the solution is neutral;

[0032] (3) When the ferric nitrate-citrate mixed solution is in a colloidal state, 0.1 to 0.3 g of ultrasonically dispersed micro-expanded microcrystalline graphite is added, and heating and stirring are continued until the water is evaporated to obtain a composite material precursor;

[0033] (4) placing the prepared precursor into an Ar gas protected tubular furnace, heating it to 300-400°C at a rate of 5-7°C / min, keeping it at that temperature for 1-2h, and cooling it to room temperature to prepare micro-expanded microcrystalline graphite / Fe3O4 composite materials with different Fe3O4 mass fractions;

[0034] (5) Weigh 0.5-2 g of micro-expanded microcrystalline graphite / Fe3O4 composite material, disperse it in 20-50 ml of anhydrous ethanol, and ultrasonicate it for 20-50 min;

[0035] (6) Weigh 0.2-0.8 g of ammonium molybdate and 0.0035-0.0087 g of citric acid and add 20-40 ml of deionized water, and sonicate until completely dissolved;

[0036] (7) stirring in a water bath at 60-90° C., adding the micro-expanded microcrystalline graphite / Fe3O4 composite material dispersed in step (5) and continuing to stir until the water is evaporated;

[0037] (8) drying in a vacuum oven at 50-80°C;

[0038] (9) placing the prepared coating material in an Ar gas protected tubular furnace, heating it to 200-460° C. at a rate of 5-7° C. / min, keeping it warm for 1-2 h, and naturally cooling it to room temperature to obtain a MoO3 / C co-coated micro-expanded microcrystalline graphite / Fe3O4 composite material;

[0039] (10) Micro-expanded microcrystalline graphite / Fe3O4 composite materials and MoO3 / C co-coated micro-expanded microcrystalline graphite / Fe3O4 composite materials are used as negative electrode materials for lithium-ion batteries.

[0040] Example 1: Weigh 0.3 g of ferric nitrate, add 20 ml of deionized water, and ultrasonicate for 30 minutes; add 0.3 g of citric acid, stir in a 50°C magnetic stirring water bath, and add ammonia water dropwise until the solution is neutral; when the ferric nitrate and citric acid mixed solution is in a colloidal state, add 0.1 g of ultrasonically dispersed micro-expanded microcrystalline graphite, continue heating and stirring until the water evaporates to dryness, thereby obtaining a composite material precursor; put the prepared precursor into an Ar gas-protected tubular furnace, heat to 300°C at a rate of 5°C / min, keep warm for 1 hour, and cool to room temperature, and use this sol-gel method to prepare micro-expanded microcrystalline graphite / Fe3O4 composite materials with different Fe3O4 mass fractions as negative electrode materials for lithium-ion batteries;

[0041] Weigh 0.5g of micro-expanded microcrystalline graphite / Fe3O4 composite material, disperse it in 20ml of anhydrous ethanol, and ultrasonicate for 20min; weigh 0.5g of ammonium molybdate and 0.0036g of citric acid and add them to 20ml of deionized water, and ultrasonicate until completely dissolved; stir in a 60℃ water bath, then add the dispersed micro-expanded microcrystalline graphite / Fe3O4 composite material and continue stirring until the water is evaporated; dry in a vacuum oven at 50℃; put the prepared coating material into an Ar gas-protected tubular furnace, heat it to 200℃ at a rate of 5℃ / min, keep it warm for 1h, and naturally cool it to room temperature. Use this liquid phase coating method to prepare MoO3 / C co-coated micro-expanded microcrystalline graphite / Fe3O4 composite material as a negative electrode material for lithium-ion batteries.

[0042] like Figure 1 As shown in the figure, the microstructure morphology of the micro-expanded microcrystalline graphite / Fe3O4 composite material is prepared, and white nano-Fe3O4 particles are distributed on the surface of the micron-oxidized microcrystalline graphite, especially on the boundary. Figure 2 As shown in the figure, the microstructure morphology of the MoO3 / C co-coated micro-expanded microcrystalline graphite / Fe3O4 composite material is prepared. After coating, the material boundary is smoother, and the holes and cracks on the surface and edge of the micro-expanded microcrystalline graphite / Fe3O4 are gradually covered by MoO3 / C microspheres.

[0043] Comparative Example 1: According to the sol-gel method in Example 1, 0.6 g of ferric nitrate and 0.3 g of citric acid were weighed, and the rest of the operation process was the same as in Example 1.

[0044] Comparative Example 2: According to the sol-gel method in Example 1, 0.3 g of ferric nitrate and 0.4 g of citric acid were weighed, and the rest of the operation process was the same as in Example 1.

[0045] Comparative Example 3: According to the sol-gel method in Example 1, 0.2 g of micro-expanded microcrystalline graphite was weighed, and the rest of the operation process was the same as in Example 1.

[0046] Comparative Example 4: According to the sol-gel method in Example 1, 0.3 g of micro-expanded microcrystalline graphite was weighed, and the rest of the operation process was the same as in Example 1.

[0047] Table 1 Electrochemical properties of micro-expanded microcrystalline graphite / Fe3O4 composites

[0048]

[0049] Table 2 Electrochemical properties of MoO3 / C co-coated micro-expanded microcrystalline graphite / Fe3O4 composites

[0050]

[0051]

[0052] Example 2: Weigh 0.6 g of ferric nitrate, add 40 ml of deionized water, and ultrasonicate for 40 min; add 0.2 g of citric acid, stir in a 70°C magnetic stirring water bath, and add ammonia water dropwise until the solution is neutral; when the ferric nitrate citric acid mixed solution is colloidal, add 0.3 g of ultrasonically dispersed micro-expanded microcrystalline graphite, continue heating and stirring until the water evaporates to obtain a composite material precursor; put the prepared precursor into an Ar gas protected tubular furnace at 6°C·min -1 The temperature was raised to 400°C at a speed of 100 °C, kept at this temperature for 2 hours, and cooled to room temperature. The micro-expanded microcrystalline graphite / Fe3O4 composite materials with different Fe3O4 mass fractions were prepared by the sol-gel method as negative electrode materials for lithium-ion batteries.

[0053] Weigh 2g of micro-expanded microcrystalline graphite / Fe3O4 composite material, disperse it in 50ml of anhydrous ethanol, and ultrasonicate for 30min; weigh 0.3g of ammonium molybdate and 0.0057g of citric acid and add them to 40ml of deionized water, and ultrasonicate until completely dissolved; stir in an 80℃ water bath, then add the dispersed micro-expanded microcrystalline graphite / Fe3O4 composite material and continue stirring until the water evaporates; dry in a vacuum oven at 80℃; put the prepared coating material into an Ar gas-protected tubular furnace and heat at 6℃·min -1 The temperature was raised to 400°C at a rate of 100 °C, kept at that temperature for 2 hours, and naturally cooled to room temperature. The MoO3 / C co-coated micro-expanded microcrystalline graphite / Fe3O4 composite material was prepared by this liquid phase coating method as a negative electrode material for lithium-ion batteries.

[0054] Comparative Example 5: According to the sol-gel method in Example 2, 0.2 g of microcrystalline graphite is weighed, and according to the liquid phase coating method in Example 2, 1 g of micro-expanded microcrystalline graphite / Fe3O4 composite material is weighed, and the rest of the operation process is the same as Example 2.

[0055] Comparative Example 6: According to the sol-gel method in Example 2, 0.1 g of microcrystalline graphite is weighed, and according to the liquid phase coating method in Example 2, 0.5 g of micro-expanded microcrystalline graphite / Fe3O4 composite material is weighed, and the rest of the operation process is the same as Example 2.

[0056] Comparative Example 7: According to the sol-gel method in Example 2, 0.3 g of ferric nitrate and 0.4 g of citric acid were weighed; according to the liquid phase coating method in Example 2, 0.5 g of ammonium molybdate and 0.0087 g of citric acid were weighed; the rest of the operation process was the same as in Example 2.

[0057] Comparative Example 8: According to the sol-gel method in Example 2, 0.4 g of ferric nitrate and 0.3 g of citric acid were weighed; according to the liquid phase coating method in Example 2, 0.8 g of ammonium molybdate and 0.0035 g of citric acid were weighed; the rest of the operation process was the same as in Example 2.

[0058] Table 3 Electrochemical properties of expanded microcrystalline graphite / Fe3O4 composites

[0059]

[0060] Table 4 Electrochemical properties of MoO3 / C co-coated micro-expanded microcrystalline graphite / Fe3O4 composites

[0061]

[0062] In the present invention, the lithium ion battery test conditions are: using Shenzhen Xinweier BTS-5V / 2.2A battery test equipment, constant temperature 25°C, and test voltage range of 0.01-3V. It can be seen from Tables 1 to 4 that the micro-expanded microcrystalline graphite / Fe3O4 composite material prepared by the sol-gel method is used as a negative electrode material for lithium-ion batteries. At a current density of 0.1A / g, the first discharge specific capacity is 860.3mAh / g, the first coulomb efficiency is 78.6%, and after 100 cycles, the reversible specific capacity of the composite material is 765.3mAh / g, and the capacity retention rate is 89.0%; the MoO3 / C co-coated micro-expanded microcrystalline graphite / Fe3O4 composite material prepared by the liquid phase coating method is used as a negative electrode material for lithium-ion batteries. At a current density of 0.1A / g, the first charge and discharge specific capacity is 987.3mAh / g, the first coulomb efficiency is 81.6%, and after 100 cycles, it still has a reversible specific capacity of 853.2mAh / g, and the capacity retention rate is 86.4%.

[0063] The above is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and changes can be made without departing from the principle of the present invention, and these improvements and changes are also regarded as the protection scope of the present invention.

Claims

1. A method for preparing a MoO3 / C co-coated micro-expanded microcrystalline graphite / Fe3O4 lithium ion battery negative electrode material, characterized in that: include: Micro-expanded microcrystalline graphite / Fe3O4 composite materials were prepared by sol-gel method with micro-expanded microcrystalline graphite as matrix. Then, the micro-expanded microcrystalline graphite / Fe3O4 composite material was used as the matrix and the MoO3 / C co-coated micro-expanded microcrystalline graphite / Fe3O4 composite material was prepared by using a liquid phase coating method by changing the addition amounts of ammonium molybdate and citric acid.

2. The method for preparing the MoO3 / C co-coated micro-expanded microcrystalline graphite / Fe3O4 lithium ion battery negative electrode material according to claim 1, characterized in that the micro-expanded microcrystalline graphite / Fe3O4 composite material is prepared by a sol-gel method, comprising the following steps: Step (1): weigh 0.3-0.6 g of ferric nitrate, add 20-40 ml of deionized water, and sonicate for 30-40 min; Step (2): add 0.1-0.4 g of citric acid, stir in a magnetic stirring water bath at 50-70° C., and add ammonia water dropwise until the solution is neutral; Step (3): When the ferric nitrate-citrate mixed solution is in a gelatinous state, 0.1 to 0.3 g of ultrasonically dispersed micro-expanded microcrystalline graphite is added, and heating and stirring are continued until the water is evaporated to dryness, thereby obtaining a composite material precursor; Step (4): Place the prepared precursor into an Ar gas protected tubular furnace, heat it to 300-400°C at a rate of 5-7°C / min, keep it warm for 1-2h, and cool it to room temperature to prepare micro-expanded microcrystalline graphite / Fe3O4 composite materials with different Fe3O4 mass fractions.

3. The method for preparing the MoO3 / C co-coated micro-expanded microcrystalline graphite / Fe3O4 lithium ion battery negative electrode material as described in claim 2, characterized in that the microcrystalline graphite is micron-sized microcrystalline graphite with a micro-expanded boundary of about 5 μm, and the Fe3O4 prepared in step (4) is a nano-sized particle, and the two form a micro-nano composite structure.

4. The method for preparing the MoO3 / C co-coated micro-expanded microcrystalline graphite / Fe3O4 lithium ion battery negative electrode material according to claim 1, characterized in that: The liquid phase coating method prepares the MoO3 / C co-coated micro-expanded microcrystalline graphite / Fe3O4 composite material by changing the addition amount of ammonium molybdate and citric acid, and comprises the following steps: Step (1): weigh 0.5-2 g of micro-expanded microcrystalline graphite / Fe3O4 composite material, disperse it in 20-50 ml of anhydrous ethanol, and ultrasonicate it for 20-50 min; Step (2): weigh 0.2-0.8 g of ammonium molybdate and 0.0035-0.0087 g of citric acid, add 20-40 ml of deionized water, and sonicate until completely dissolved; Step (3): stirring in a water bath at 60-90° C., adding the dispersed micro-expanded microcrystalline graphite / Fe3O4 composite material and continuing to stir until the water is evaporated; Step (4): drying in a vacuum oven at 50-80°C; Step (5): placing the prepared coating material into an Ar gas protected tubular furnace, heating it to 200-460°C at a rate of 5-7°C / min, keeping it warm for 1-2 hours, and naturally cooling it to room temperature to obtain a MoO3 / C co-coated micro-expanded microcrystalline graphite / Fe3O4 composite material.

5. The MoO3 / C co-coated micro-expanded microcrystalline graphite / Fe3O4 composite material prepared by the preparation method as described in any one of claims 1 to 4.

6. Use of the micro-expanded microcrystalline graphite / Fe3O4 composite material as claimed in claim 1 or 2 in the negative electrode of a lithium ion battery.

7. Use of the MoO3 / C co-coated micro-expanded microcrystalline graphite / Fe3O4 composite material prepared as claimed in claim 5 in the negative electrode of a lithium ion battery.

Citation Information

Patent Citations

  • Preparation method of lithium ion battery molybdenum oxide carbon composite cathode material

    CN102569813A

  • Method for preparing ferriferrous oxide magnetic material and composite material thereof

    CN105271431A

  • Negative Electrode Active Material and Negative Electrode for Solid State Battery Including the Same

    US20200411843A1

Cited By

  • Preparation method of lithium ion battery negative electrode material

    CN122025576A